Algarve Cervical Cancer Screening Programme. (13th November 2019) - Correia, M; Pacheco, A; Morera, J; Pereira, R; Ferrinho, D; Vale, L; Cardoso, C
Abstract: Issue: Cervical Cancer (CC) is the 7th most frequent and the 2nd most common in women. The standardized mortality rate, in Portugal is 2.3/100000 inhabitants and Algarve is the region with highest rate, 4.9/100000. Description: Programme started in 2010. Population-based screening programme can reduce incidence, mortality and morbidity with an early diagnosis, preventing aggressive interventions in precancerous phase, improving survival and life quality. Target population, woman age 25-64.are invited to primary test liquid-based cytology (ThinPrep) every 3 years. Health Centres are responsible for select, invite, collect samples and send to Hospital laboratory. For positives, a cervical pathology consultation is required. National Guidelines now indicates DNA testing for human papillomavirus (HPV) as primary screening test, each 5 years, to woman age 25 to 60 and screening program changes will be implemented in 2019 with improved response time and lower cost. Results: Since 2010 the target population has increased 12% every 2 years and the adhesion rate increased ≈68% and≈108%. Nevertheless the 3rd cycle has showed 10, 8% (17.975) adhesion rate. Most women 16.112 (89.6%) had a negative diagnosis, 503 (2, 8%) is ASC-US + (HPV test), and 761(4, 2%) had a cervical pathology consultation. From those, 117 (15.4%) had a LSIL, 69 (9, 1%) HSIL and 2(0, 3%) cancer. Cancer detection rate is 0, 1 ‰. Lessons: The small adhesion rate particularly by aged women, the users unfriendly Information System and direct screening health units management are some of the issues that requires improvement. Also population literacy, self-sampling vaginal fluid and clinical meetings are some of the options to improve screening program. Key messages: Cervical Cancer early diagnosis prevent aggressive interventions in a precancerous phase, improves survival and life quality. Better access and health communication are major points in screening programs.